2022
DOI: 10.1097/nmd.0000000000001601
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among Autistic Traits, Impulsivity, and Functionality in Patients With Obsessive-Compulsive Disorder

Abstract: Obsessive-compulsive disorder (OCD) is a chronic mental disorder that causes disabilities. This study investigated the relationship among impulsivity, autistic traits, and disabilities in patients with OCD. We included 88 patients with OCD and 90 healthy volunteers without any mental disorders. The participants were evaluated using the Yale-Brown Obsessive-Compulsive Scale, Autism Spectrum Quotient (AQ), Barratt Impulsiveness Scale-11 (BIS-11), and World Health Organization Disability Assessment Schedule (WHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…OCD is a mental illness characterized by the presence of obsessions and/or compulsions, which are time-consuming or cause clinically significant distress or functional impairment [ 1 ]. It has been reported that ASD traits are more common in persons with OCD than in healthy population and are associated with poor functioning in OCD [ 14 ]. Obsessions in OCD are sometimes similar as restricted interests in ASD, while compulsions in OCD are often likened to repetitive behaviors in ASD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…OCD is a mental illness characterized by the presence of obsessions and/or compulsions, which are time-consuming or cause clinically significant distress or functional impairment [ 1 ]. It has been reported that ASD traits are more common in persons with OCD than in healthy population and are associated with poor functioning in OCD [ 14 ]. Obsessions in OCD are sometimes similar as restricted interests in ASD, while compulsions in OCD are often likened to repetitive behaviors in ASD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%